Pengasuhan Qurani untuk Mencegah Kekerasan Seksual Anak: Studi Tafsir Tematik QS. An-Nur: 30-31 - Fakhirah, Nadiatun; Haris, Abdul Rauf (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
The surge in cases of sexual violence against children in Indonesia has led to studies aiming to identify preventive measures based on the principles of the Quran. The research aims to describe the concept of Qur’anic parenting based on QS. An-Nur: 30-31 as an effort to prevent sexual violence against boys and girls. Using thematic interpretation (tafsir maudhu’i), this study analyzes relevant verses based on authoritative tafsir references, such as Tafsir Al-Munir, Ibnu Katsir, and As-Sa’di. The research findings indicate that the concept of Qur'anic parenting based on QS An-Nur: 30-31 aims to create a safe and controlled environment to preserve human nature (fitrah) while protecting children from the risk of sexual violence. This is achieved by establishing several behavioral norms or guidelines for both boys and girls. These behavioral guidelines include lowering the gaze, covering the aurah, safeguarding chastity, instilling awareness of Allah’s supervision (muroqabah), and maintaining obedience and repentance. Specifically for girls, additional measures include the obligation to wear the hijab, avoid fitnah, and refrain from seeking the attention of the opposite gender. These behaviors serve a purpose and have benefits in preventing the occurrence of sexual violence against children.